Experimental study of sheathed cold-formed steel beam–columns. (September 2021) - Kyprianou, Constantinos; Kyvelou, Pinelopi; Gardner, Leroy; Nethercot, David A.
Abstract: An experimental study of sheathed cold-formed steel C-lipped wall studs, with service holes, subjected to compression and major axis bending is presented in this paper. A total of 17 experiments were performed with both oriented strand board (OSB) and plasterboard used as sheathing and with varying connector spacing employed between the sheathing panels and the steel members. The tested specimens comprised a single 2.4 m long column sheathed on both sides and secured at the ends to top and bottom tracks. The member tests were complemented by material tests, stub column tests and initial geometric imperfection measurements. The specimens were tested in a dual-actuator rig where axial compression was applied by means of a vertical actuator through the top track, while bending was applied through the application of four lateral point loads. Eight pure compression tests with both plasterboard and OSB sheathing and with the spacing of the connectors varying between 75 mm and 600 mm were initially performed. Specimens with OSB sheathing were then tested under pure bending and combined loading. The full load–deformation responses and failure modes of the member test specimens are reported. The compressed studs connected to the plasterboard sheathing at wider spacings exhibited pull-through failure of the connectors, followed by flexural torsional buckling, while the specimens with denser connector spacings, failed by local buckling at the member ends. The OSB sheathed specimens under pure compression failed by local and distortional buckling, those under combined loading exhibited local failure at the service openings, while for those under pure bending, local buckling and stud-to-track connector failure occurred. Reducing the spacing of the connectors from 600 mm to 75 mm resulted in up to 20% and 30% increases in capacity for the studs sheathed with OSB and plasterboard respectively. Highlights: Seventeen full-scale tests on sheathed cold-formed steel members were conducted. The tests included eight specimens under pure compression. The tests included six specimens under combined compression and bending. The tests included three specimens under pure bending. The tested specimens were sheathed with either plasterboard or OSB. Sheathing was connected on both sides of the member at various screw spacings. Initial geometric imperfection measurements were carried out. Reducing the screw spacing from 600 mm to 75 mm led up to 30% capacity increases.